Effect of Oats and Oat-Fiber on Glycemic Control in Diabetes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (7th June 2021) - Chen, Victoria; Zurbau, Andreea; Ahmed, Amna; Khan, Tauseef; Kendall, Cyril; Sievenpiper, John
Abstract: Objectives: Current approved health claims in Canada, US and Europe recognize the ability of oat ß-glucan to lower blood cholesterol; however, its ability to improve glycemic control is less certain. We undertook a systematic review and meta-analysis of randomized controlled trials to update the evidence of the effect of oats and oat-fiber on markers of glycemic control in people with and without diabetes. Here we present data for the subgroup with diabetes. Methods: MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were searched through September 23 rd, 2020. We included randomized controlled trials of ≥ 2-weeks of sources of oat ß-glucan and measures of glycemic control in diabetes. Two independent reviewers extracted relevant data and assessed the risk of bias (Cochrane Risk of Bias 2.0 Tool). The outcomes were fasting plasma glucose (FPG), 2h-plasma glucose (2h-PG) from a 75 g-oral glucose tolerance test, HbA1c and fasting plasma insulin (FPI). Data were pooled using the generic inverse variance method. Heterogeneity was assessed (Cochran Q statistic) and quantified (I 2 statistic). Pooled estimates were expressed as mean differences with 95% confidence intervals (CI). GRADE assessed the certainty of the evidence. Results: Eligibility criteria were met by 5 trial comparisons (N = 359) in type 2 diabetes. No trials were identified in type 1 diabetes. Consumption of oat ß-glucan sources reduced FPG (MD = −0.37 mmol/L [95% CI: −0.70, −0.05 mmol/L], P = 0.03, I 2  = 0.00%, PQ  = 0.76) and 2h-PG (MD = −1.24 mmol/L [95% CI: −1.97, −0.51 mmol/L], P = 0.00, I 2  = 0.00%, PQ  = 0.56). There were non-significant reductions in HbA1c (MD = −0.12%, [95% CI: −0.26, 0.01%], P = 0.07, I 2  = 0.00%, PQ  = 1.00) and FPI (MD = −4.59 pmol/L, [95% CI: −14.71, 5.52 pmol/L], P = 0.37, I 2  = 40.84%, PQ  = 0.19). The certainty of evidence was high for 2h-PG and moderate for FPG, HbA1c and FPI (single downgrades for imprecision in each case). Conclusions: Current evidence provides a good indication that consumption of oat ß-glucan results in small improvements of glycemic control in type 2 diabetes. More high quality randomized trials are required to improve the precision of the pooled estimates. (ClinicalTrials.gov identifier, NCT04631913) Funding Sources: Quaker Oats Center of Excellence, Diabetes Canada, Banting & Best Diabetes Centre, Toronto 3D foundation